2019
DOI: 10.1089/jamp.2018.1463
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Flow Rate Dependency of Delivered Dose and Fine Particle Dose of Salmeterol/Fluticasone Propionate Easyhaler and Seretide Diskus with Patient Flow Rates Collected in a Randomized Controlled Trial

Abstract: Background: The Easyhaler ® device-metered dry powder inhaler containing Salmeterol and Fluticasone propionate (S/F) has been developed for the treatment of patients with asthma and chronic obstructive pulmonary disease (COPD). We report two studies which evaluated the in vitro flow rate dependence of delivered dose (DD) and fine particle dose (FPD) of S/F Easyhaler versus Seretide Diskus ® . Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 22 publications
1
32
0
1
Order By: Relevance
“…As this was originally intended as a method in quality control in the context of batch release, it is ill suited to produce data relevant to performance with patients. Recent publications are instead reporting the use of fixed ranges of inspiratory flow rates or patient population-specific percentiles when trying to simulate real-life conditions [18, 20, 27]. Haidl et al [28] have suggested criteria for a successful inhalation manoeuvre, namely sufficient device-specific inhalation flow rate, flow acceleration, inhalation volume and inhaled volume after actuation.…”
Section: From Powder To Aerosolmentioning
confidence: 99%
“…As this was originally intended as a method in quality control in the context of batch release, it is ill suited to produce data relevant to performance with patients. Recent publications are instead reporting the use of fixed ranges of inspiratory flow rates or patient population-specific percentiles when trying to simulate real-life conditions [18, 20, 27]. Haidl et al [28] have suggested criteria for a successful inhalation manoeuvre, namely sufficient device-specific inhalation flow rate, flow acceleration, inhalation volume and inhaled volume after actuation.…”
Section: From Powder To Aerosolmentioning
confidence: 99%
“…The amount of active drug collected into the sampling apparatus was determined by high performance liquid chromatography (HPLC), as described earlier. (15) APSD and FPD. APSD was determined using a nextgeneration impactor (NGI) equipped with a preseparator, in accordance with the European Pharmacopoeia 9.0.…”
Section: Assessmentsmentioning
confidence: 99%
“…The NGI results of dropping and vibration tests were also expressed as lg/inhalation for each stage. (15) All analyses were performed using Microsoft Excel (Office Professional Plus 2016; Microsoft Corporation, Redmond, Washington).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A nebulizer provides a convenient method for the pulmonary delivery of a wide range of drugs, including drug doses too large for delivery by other inhaler devices and combinations of different compatible drugs, especially for the elderly and children's medication. 5,6 Notably, various nebulizers (e.g. conventional jet, ultrasonic and vibrating mesh nebulizers) with different properties are widely used in the clinic.…”
Section: Introductionmentioning
confidence: 99%